Bone mechanics matching shell-imitating structure bioactive ceramic-based composite material as well as preparation method and application thereof

Through the preparation of an ordered layered porous structure bioceramic matrix composite material imitating shell structure, the problems of high brittleness and high modulus of traditional bioceramic materials are solved, and the mechanical properties of high strength, high toughness and low modulus are achieved, and good biocompatibility and biological activity are good, and suitable for bone repair materials.

CN119524210APending Publication Date: 2025-02-28SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411722285.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional bioceramic materials are difficult to have both high strength, high toughness and low modulus due to their high brittleness and high modulus mechanical properties, resulting in poor bone matching. After implantation into the body, it is easy to produce "stress shielding" phenomenon, weakening the bone repair effect.

Method used

The ordered layered porous structure bioceramic matrix composite material with a shell structure is adopted. The mixture of calcium permeable phosphite powder, polyvinyl alcohol and sodium polyacrylate is carried out, and the bidirectional freezing, freeze-drying and vacuum infiltration processes are carried out, and the mixture of methyl methacrylate-acrylic acid-benzoyl peroxide polymer is filled with a mixed solution of methyl methacrylate-acrylic acid-benzoyl peroxide polymer was precured, press-forming and secondary curing, and a bioceramic matrix composite material with mechanical characteristics of high strength, high toughness, low modulus is prepared.

Benefits of technology

The comprehensive mechanical properties of high strength, high toughness and low modulus of bioceramic materials have been achieved, and the problem of poor bone matching of traditional bioceramic materials has been overcome, and it has good biocompatibility and biological activity, which can continuously release Ca and P biologically active ions, and promote bone repair and regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524210A_ABST
    Figure CN119524210A_ABST
Patent Text Reader

Abstract

The invention relates to a bone mechanics matching shell-imitating structure bioactive ceramic-based composite material as well as a preparation method and application thereof. The osteomechanics matching shell-imitating structure bioactive ceramic-based composite material comprises an ordered layered porous structure biological ceramic matrix and biocompatible high polymer materials which are uniformly distributed on the surface and inside the ordered layered porous structure biological ceramic matrix, a biological ceramic element of the ordered layered porous structure biological ceramic matrix comprises brushite powder, an aluminum oxide nanosheet, a hydroxyapatite microrod, a calcium silicate nanowire or a graphene oxide nanosheet, and preferably the brushite powder; the biocompatible high polymer material comprises at least one of polymethyl methacrylate, polyvinyl alcohol, sodium polyacrylate, polyacrylamide and sodium alginate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of bioceramic materials, and in particular relates to a bioactive ceramic-based composite material with a bone mechanics matching shell-like structure, and a preparation method and application thereof. Background Art

[0002] Human bone tissue is a natural material with excellent comprehensive mechanical properties, high strength (50-150MPa), high toughness (fracture toughness of 2-12MPam 1 / 2 ) and low modulus (2-25GPa) and other mechanical properties. The ideal load-bearing bone defect repair material should have high strength and toughness mechanical characteristics that match natural load-bearing bones, and should also have good biocompatibility, degradability and bioactivity to meet the needs of load-bearing bone defect repair in vivo.

[0003] Bioceramics are a type of biomaterial with good biocompatibility and bioactivity, with the advantages of adjustable components and abundant sources. However, traditional high-temperature sintered bioceramics have great brittleness and high modulus, and it is difficult to have the mechanical properties of high strength, high toughness and low modulus, resulting in poor bone matching. After implantation in the body, it is easy to produce "stress shielding" phenomenon, thereby weakening the bone repair effect. Therefore, it is of great practical significance to prepare bioceramics with good bioactivity and mechanical properties matching natural bone tissue.

[0004] Shells are currently the most widely studied natural high-strength structural composite material, composed of 95% flaky calcium carbonate and 5% organic matter between the lamellae, with an orderly arranged "brick-mud" layered structure. However, shells have much higher strength and toughness than calcium carbonate, and their ordered "brick-mud" layered structure is considered to be the main reason for their high toughness. During the fracture process, this ordered "brick-mud" layered microstructure can provide a variety of failure mechanisms such as crack tip plastic deformation, crack deflection, and lamellar slip, greatly increasing the energy absorbed and dissipated by material failure, thereby improving strength and toughness.

[0005] Therefore, the preparation of bioceramic-based materials with an ordered "brick-mud" layered structure that mimics shells will hopefully enable ceramic materials to have both high strength and high toughness, solving the problem that traditional ceramic materials cannot have both high strength, high toughness and low modulus, and providing inspiration for the design of the structure and mechanical properties of artificial bone materials. Summary of the invention

[0006] In view of the problem of large brittleness and high modulus of bioceramics, the present invention provides a method for preparing a bioactive ceramic-based composite material with a shell-like structure that matches bone mechanics and its application in bone tissue repair. The ceramic-based composite material has the mechanical characteristics of high strength, high toughness and low modulus, and has comprehensive mechanical properties that match the load-bearing bones of the human body. It can still meet the mechanical strength required for the repair of load-bearing bone defects in a wet state, making up for the shortcomings of traditional bioceramic materials such as brittleness and poor toughness, and overcoming the problem of poor bone matching of traditional bioceramic materials. In addition, the shell-like structure bioceramic-based composite material has good biocompatibility and bioactivity, and promotes the proliferation of bone marrow mesenchymal stem cells by continuously releasing Ca and P bioactive ions. After implantation in the body, it integrates well with defective bone tissue and has good clinical application prospects.

[0007] In a first aspect, the present invention provides a bone mechanics matching shell-like structure bioactive ceramic-based composite material, the bone mechanics matching shell-like structure bioactive ceramic-based composite material comprising: an ordered layered porous structure bioceramic matrix, and a biocompatible polymer material uniformly distributed on the surface and inside of the ordered layered porous structure bioceramic matrix; the bioceramic elements of the ordered layered porous structure bioceramic matrix include brushite powder, aluminum oxide nanosheets, hydroxyapatite microrods, calcium silicate nanowires or graphene oxide nanosheets, preferably brushite powder; The biocompatible polymer material includes at least one of polymethyl methacrylate, polyvinyl alcohol, sodium polyacrylate, polyacrylamide and sodium alginate.

[0008] Preferably, based on the total mass of the bone mechanics matching shell-like structure bioactive ceramic-based composite material as 100%, the mass of the ordered layered porous structure bioceramic matrix accounts for 70-75%, and the mass of the biocompatible polymer material accounts for 25-30%; Preferably, the mass proportion of the brushite matrix of the ordered layered porous structure is 70-75%, the mass proportion of polymethyl methacrylate is 8-10%, and the mass proportion of polyvinyl alcohol and sodium polyacrylate is 17-20%.

[0009] Preferably, the flexural strength of the bone mechanics matching shell-like structure bioactive ceramic matrix composite material is 60-140MPa, preferably 119.3±5MPa; the elastic modulus is 2-7.5GPa, preferably 6.8±0.4GPa; the fracture work is 0.82-1.75kJ / m 2 , preferably 1.15±0.33 kJ / m 2 .

[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned bone mechanics matching shell-like structure bioactive ceramic-based composite material, the preparation method comprising the following steps: (1) mixing brushite powder, polyvinyl alcohol solution and sodium polyacrylate solution to obtain brushite ceramic slurry; (2) subjecting the brushite ceramic slurry to bi-directional freezing and freeze drying to obtain a brushite matrix template with an ordered layered porous structure; (3) Filling the ordered layered porous structured brushite matrix template with a methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution through a vacuum infiltration process and pre-curing, and then pressing, secondary curing, and drying to obtain the bone mechanics matching shell-like structure bioactive ceramic-based composite material.

[0011] Preferably, in step (1), the brushite powder is prepared by the following process: potassium dihydrogen phosphate, disodium hydrogen phosphate and anhydrous calcium chloride are added to ultrapure water in sequence, a precipitation reaction occurs in the solution to generate brushite micron flakes, and the brushite ceramic powder is obtained by suction filtration, drying, grinding and dispersion; wherein the mass ratio of the ultrapure water, potassium dihydrogen phosphate, disodium hydrogen phosphate and anhydrous calcium chloride is 0.9-3.6L:0.825-3.3g:3.0095-12.038g:3.031-12.124g, preferably 1.8L:1.650g:6.019g:6.062g; In the brushite ceramic slurry, the mass fraction of brushite is 10-30%, preferably 10%; the mass fraction of polyvinyl alcohol is 1-5%, preferably 2%; and the mass fraction of sodium polyacrylate is 0.5-1%, preferably 1%.

[0012] Preferably, in step (2), the bi-directional freezing is carried out in a mold with the aid of a wedge-shaped polydimethylsiloxane block; preferably, the angle of the wedge-shaped polydimethylsiloxane used for the bi-directional freezing can be 10-20°, more preferably 15°; the temperature of the bi-directional freezing is -100 to -180°C, and the time of the bi-directional freezing is 0.5-2h.

[0013] Preferably, in step (3), in the methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution, based on the total mass of methyl methacrylate and acrylic acid as 100%, the mass fraction of methyl methacrylate can be 90-95%, preferably 95%, and the mass fraction of acrylic acid is 5-10%, preferably 5%; the mass fraction of the initiator benzoyl peroxide can be 2-4%, preferably 2%, of the total mass of methyl methacrylate and acrylic acid.

[0014] Preferably, in step (3), the vacuum infiltration process is: placing the ordered layered porous structure brushite matrix template in a centrifuge tube and adding a methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution, and then placing them in a vacuum drying oven, and evacuating them at 25-30° C. and 80-100 Pa vacuum for 7-9 hours; The pre-curing is carried out under normal atmospheric pressure, at a temperature of 40-50°C, for 6-8 days, preferably 7 days; The pressing process is: taking out the pre-cured block template material and pressing the block template material along a direction perpendicular to the layered structure using a powder tablet press; wherein the pressing pressure is 125-305MPa, preferably 301MPa, and the pressing time is 10-30min.

[0015] Preferably, in step (3), the secondary curing process comprises: placing the pressed ordered layered porous structure brushite matrix template in a methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution, and then placing them in a vacuum drying oven, evacuating for 3-5 hours at 25-30° C. and 80-100 Pa vacuum degree to allow the MMAA polymer mixed solution to further penetrate into the block template material, and then continuing to cure at 40-50° C. and normal atmospheric pressure for 6-8 days until the MMAA polymer mixed solution is cured into a solid state.

[0016] In a third aspect, the present invention provides an application of the above-mentioned bone mechanics matching shell-like structure bioactive ceramic-based composite material in the preparation of bone repair materials.

[0017] Beneficial Effects (1) Inspired by the "brick-mud" layered structure of natural shell nacre, the present invention uses brushite micron sheets as the base material and combines the method of dual-directional freezing-freeze drying-polymer infusion polymerization-pressure densification to prepare a shell-like bioactive ceramic-based composite material with an ordered layered microstructure; (2) The ceramic matrix composite material provided by the present invention has the mechanical characteristics of high strength, high toughness and low modulus (flexural strength is 119.3±5MPa, elastic modulus is 6.8±0.4GPa, fracture work is 1.15±0.33kJ / m 2 ), has comprehensive mechanical properties that match those of human body’s load-bearing bones, and can still meet the mechanical strength required for repairing load-bearing bone defects in a wet state, overcoming the stress shielding problem caused by the excessively high modulus of traditional sintered bioceramics, as well as the defects of brittleness and poor toughness of traditional ceramic materials; (3) The shell-like structure bioceramic-based composite material provided by the present invention has good biocompatibility and bioactivity, can continuously release two bioactive ions of Ca and P, has improved proliferation activity of bone marrow mesenchymal stem cells and enhances their osteogenic differentiation. The prepared shell-like structure bioceramic-based composite material is a high-strength, high-toughness, low-modulus bioceramic-based structural material with both bone mechanical matching and bioactivity, has potential application prospects in the repair of large-segment load-bearing bone defects, and also provides a simple, feasible and universal design concept and preparation strategy for the development of high-strength bone repair materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a microscopic morphology of the brushite ceramic powder prepared in Example 1, and the inserted picture in Figure A is an optical photograph of the brushite ceramic powder; Figure 2 The crystal phase analysis diagram and thermogravimetric analysis diagram of the brushite ceramic powder prepared in Example 1; wherein A is the XRD spectrum of brushite, and B is the thermogravimetric curve of brushite; Figure 3 Optical photographs and microscopic morphologies of the ordered layered porous structure brushite matrix with different brushite mass fractions obtained by bidirectional freezing-freeze drying in Examples 1-3 and the disordered structure brushite matrix obtained by -80°C freezing-freeze drying in Comparative Example 1; wherein A1-A4 are optical photographs and microscopic morphologies of the disordered structure brushite matrix, B1-B4 are optical photographs and microscopic morphologies of the ordered layered porous structure brushite matrix with a brushite mass fraction of 10%, C1-C4 are optical photographs and microscopic morphologies of an ordered layered porous structure brushite matrix with a brushite mass fraction of 20%, D1-D4 are optical photographs and microscopic morphologies of an ordered layered porous structure brushite matrix with a brushite mass fraction of 30%; E and F are optical photographs of a small-sized matrix obtained by cutting an ordered layered porous structure brushite matrix with a brushite mass fraction of 10% and an optical photograph of a letter-shaped brushite matrix obtained by cutting through a customized mold, respectively; Figure 4 The interlayer spacing (A) and porosity (B) of the ordered layered porous structure brushite matrix with different brushite (DCPD) mass fractions in Examples 1-3; Figure 5The optical photographs and microscopic morphologies of shell-like bioactive ceramic-based composite materials and disordered bioactive ceramic-based composite materials prepared under the same brushite mass fraction but different pressure conditions and under the same pressure but different brushite mass fraction conditions are shown in Figure 1; A1-A6 are optical photographs and microscopic morphologies of disordered bioactive ceramic-based composite materials, B1-B6 are optical photographs and microscopic morphologies of ordered layered porous brushite matrix with a brushite mass fraction of 10% and a pressure of 301 MPa, C1-C6 are optical photographs and microscopic morphologies of ordered layered porous brushite matrix with a brushite mass fraction of 10% and a pressure of 21 5MPa, D1-D6 are optical photographs and micromorphology of the ordered layered porous structure brushite matrix with a brushite mass fraction of 10% and a pressure of 129MPa, E1-E6 are optical photographs and micromorphology of the ordered layered porous structure brushite matrix with a brushite mass fraction of 20% and a pressure of 129MPa, and F1-F6 are optical photographs and micromorphology of the ordered layered porous structure brushite matrix with a brushite mass fraction of 30% and a pressure of 129MPa; Figure 6 for Figure 5 Thermogravimetric analysis results of different bioceramic matrix composite materials; wherein A is the thermogravimetric curve of different bioceramic matrix composite materials, and B is the actual brushite content-theoretical brushite content curve of the bioceramic matrix composite material; Figure 7 is the bending properties of bioceramic matrix composite materials with different structures / compositions; wherein, A is the bending strength of bioceramic matrix composite materials with different structures / compositions, B is the bending modulus of bioceramic matrix composite materials with different structures / compositions, C is the fracture work of bioceramic matrix composite materials with different structures / compositions, and D is the bending stress-strain curve of bioceramic matrix composite materials with different structures / compositions; Figure 8 is the bending properties of bioceramic matrix composite materials with different structures / pressing pressures; wherein, A is the bending strength of the bioceramic matrix composite materials with different structures / pressing pressures, B is the bending modulus of the bioceramic matrix composite materials with different structures / pressing pressures, C is the fracture work of the bioceramic matrix composite materials with different structures / pressing pressures, and D is the bending stress-strain curve of the bioceramic matrix composite materials with different structures / pressing pressures; Fig. 9is the bending properties of bioceramic matrix composite materials with different structures / compositions under wet conditions; wherein, A is the bending strength of bioceramic matrix composite materials with different structures / compositions under wet conditions, B is the bending modulus of bioceramic matrix composite materials with different structures / compositions under wet conditions, C is the fracture work of bioceramic matrix composite materials with different structures / compositions under wet conditions, and D is the bending stress-strain curve of bioceramic matrix composite materials with different structures / compositions under wet conditions; Fig.10 It is an analysis of the comprehensive mechanical properties of bioceramic-based composite materials under different composition / pressing pressure conditions; wherein A is the relationship between the mass fraction of brushite and the flexural strength in the bioceramic-based composite materials under different composition / pressing pressure conditions, B is the relationship between the flexural strength and the flexural modulus of the bioceramic-based composite materials under different composition / pressing pressure conditions, C is the relationship between the fracture work and the flexural strength of the bioceramic-based composite materials under different composition / pressing pressure conditions, and D is a comparison chart of the mechanical properties of the prepared shell-like structure bioceramic-based composite materials and the mechanical properties of other bone repair materials; Fig.11 The adhesion of bone marrow mesenchymal stem cells on the shell-like structure bioceramic-based composite material and the disordered structure bioceramic-based composite material; A is the immunofluorescence staining image of cells adhered to the bottom of the well plate, B is the immunofluorescence staining image of cells adhered to the disordered structure bioceramic-based composite material, and C is the immunofluorescence staining image of cells adhered to the shell-like structure bioceramic-based composite material; Fig.12 Schematic diagram of the proliferation of bone marrow mesenchymal stem cells co-cultured with shell-like structure bioceramic-based composite materials and disordered structure bioceramic-based composite materials; Fig.13 The Ca and P ion release of the shell-like structure bioceramic-based composite material and the disordered structure bioceramic-based composite material; A is the Ca ion release of the two materials, and B is the P ion release of the two materials; Fig.14 Schematic diagram of the integration of shell-like structure bioceramic-based composite materials and disordered structure bioceramic-based composite materials with native bones after implantation into rabbit skull defects. DETAILED DESCRIPTION

[0019] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0020] First, the present invention provides a bone mechanics matching shell-like structure bioactive ceramic matrix composite material. The bone mechanics matching shell-like structure bioactive ceramic matrix composite material comprises: an ordered layered porous structure bioceramic matrix, and a biocompatible polymer material uniformly distributed on the surface and inside of the ordered layered porous structure bioceramic matrix.

[0021] In some embodiments, the bioceramic elements of the ordered layered porous structure bioceramic matrix may include brushite powder, aluminum oxide nanosheets, hydroxyapatite microrods, calcium silicate nanowires or graphene oxide nanosheets, preferably brushite powder.

[0022] Wherein, the brushite has good biocompatibility and biological activity, can effectively release bioactive ions such as Ca and P, promote the proliferation of bone marrow mesenchymal stem cells, promote its osteogenic differentiation, and also have good bone repair effect in vivo. In addition, brushite is also a two-dimensional flaky bioactive ceramic, compared to other morphological materials such as nanorods, nanowires, spherical powders, etc., sheet materials have more prominent advantages when building layered structure materials, and can better form layered microstructures, similar to the flaky calcium carbonate in the shell, and the shell is also due to the extraction of flaky calcium carbonate in the failure process, the sliding and other behaviors just show good strength and toughness. The flaky brushite taken by the present invention also enhances the strength and toughness of the material, and also possesses good biological activity.

[0023] In some embodiments, the ordered layered porous structure of the brushite matrix can be controlled to have a length of not less than 20 mm, a width of not less than 5 mm, and a thickness of not less than 0.5 mm; the porosity can be 60-90%, preferably 85%. Among them, the porosity of the brushite matrix mainly depends on the mass fraction of brushite in the prepared ceramic slurry, and the matrix porosity decreases with the increase of the mass fraction of brushite, which is reflected in the gradual decrease in the interlayer spacing of the layered structure, which determines the content of methyl methacrylate, acrylic acid, benzoyl peroxide, etc. in the subsequent vacuum infiltration, and ultimately determines the comprehensive mechanical properties of the prepared shell-like structure bioceramic-based composite material.

[0024] Further, in the composite material provided by the present invention, polymethyl methacrylate etc. are reinforcements, brushite etc. are matrix, and the comprehensive mechanical properties of the composite material depend on the ratio of the matrix and the reinforcement. The present invention prepares a matrix of different porosity sizes in a certain size of mold, and then fills the materials such as polymethyl methacrylate inside the matrix, when the brushite mass fraction in the slurry used for preparing the matrix is ​​too low, the porosity of the matrix will be too high, resulting in the content of the materials such as internal polymethyl methacrylate being filled too high, so brushite cannot give play to its reinforcing effect (such as by pulling out of the sheet, crack deflection and other modes to enhance the strength of the material); on the contrary, the brushite mass fraction in the slurry is too high, and the porosity of the matrix is ​​too low, which will result in the materials such as polymethyl methacrylate being filled inside the matrix pores being too few, and even producing closed pores, resulting in polymethyl methacrylate etc. being unable to penetrate therein, so the material as a whole is not dense enough, and thus the comprehensive mechanical properties of the composite material will also be reduced. In summary, the porosity of the matrix determines the content of polymethyl methacrylate and the like that penetrates deep into the matrix, which in turn determines the ratio of the two in the composite material, thereby determining the mechanical properties of the composite material.

[0025] In some embodiments, the biocompatible polymer material may include at least one of polymethyl methacrylate, polyvinyl alcohol, sodium polyacrylate, polyacrylamide, and sodium alginate. The biocompatible polymer material mainly plays the role of a binder, which is used to maintain the structure of the matrix such as brushite and enhance the mechanical properties of the shell-like structure bioceramic-based composite material.

[0026] In some embodiments, based on the total mass of the bone mechanics matching shell-like structure bioactive ceramic-based composite material as 100%, the mass proportion of the ordered layered porous structure bioceramic matrix can be 70-75%, and the mass proportion of the biocompatible polymer material can be 25-30%; preferably, the mass proportion of the ordered layered porous structure of the brushite matrix is ​​70-75%, the mass proportion of polymethyl methacrylate is 8-10%, and the mass proportion of polyvinyl alcohol and sodium polyacrylate is 17-20%.

[0027] In some embodiments, the flexural strength of the bone mechanics matching shell-like structure bioactive ceramic-based composite material can be 60-140MPa, preferably 119.3±5MPa; the elastic modulus can be 2-7.5GPa, preferably 6.8±0.4GPa; the fracture work can be 0.82-1.75kJ / m 2 , preferably 1.15±0.33 kJ / m 2 , and has mechanical properties close to those of dense human bones.

[0028] The bone mechanical matching shell-like structure bioactive ceramic-based composite material provided by the present invention is mainly composed of matrix materials such as brushite with good biological activity. The purpose of filling with polymer materials such as polymethyl methacrylate is mainly to further regulate the mechanical properties of the bioceramic-based composite material. The role of biocompatible polymer materials such as polyvinyl alcohol and sodium polyacrylate is mainly to enhance the bonding force between brushite in the ordered layered porous structure brushite matrix, so as to enhance the mechanical properties and structural stability of the matrix such as brushite.

[0029] The following is an exemplary description of the preparation method of the above-mentioned bone mechanics matching shell-like structure bioactive ceramic-based composite material provided by the present invention. The preparation method may include the following steps: (1) mixing brushite powder, polyvinyl alcohol solution and sodium polyacrylate solution to obtain brushite ceramic slurry; (2) subjecting the brushite ceramic slurry to bi-directional freezing and freeze drying to obtain a brushite matrix template with an ordered layered porous structure; (3) Filling the ordered layered porous structured brushite matrix template with a methyl methacrylate (MMA)-acrylic acid (AA)-benzoyl peroxide (BPO) polymer mixed solution through a vacuum infiltration process and pre-curing, and then pressing, secondary curing, and drying to obtain the bone mechanics matching shell-like structure bioactive ceramic-based composite material.

[0030] In some embodiments, in step (1), the brushite powder can be prepared by the following process: potassium dihydrogen phosphate, disodium hydrogen phosphate and anhydrous calcium chloride are sequentially added to ultrapure water, a precipitation reaction occurs in the solution to generate brushite micron flakes, and the flake-shaped brushite ceramic powder is obtained by filtration, drying, grinding and dispersion.

[0031] Wherein, the mass ratio of the ultrapure water, potassium dihydrogen phosphate, sodium hydrogen phosphate and anhydrous calcium chloride can be 0.9-3.6L:0.825-3.3g:3.0095-12.038g:3.031-12.124g, preferably 1.8L:1.650g:6.019g:6.062g.

[0032] In some embodiments, in step (1), the brushite powder is in the form of flakes, with a size of 5-10 μm and a thickness of 300-500 nm.

[0033] In some embodiments, in step (1), in the brushite ceramic slurry, the mass fraction of brushite may be 10-30%, preferably 10%; the mass fraction of polyvinyl alcohol may be 1-5%, preferably 2%; and the mass fraction of sodium polyacrylate may be 0.5-1%, preferably 1%.

[0034] Among them, the higher the mass fraction of brushite in the brushite ceramic slurry, the greater the slurry viscosity and the worse the fluidity. When the mass fraction is too high, it is not conducive to forming a more regular ordered layered porous structure; on the contrary, the lower the mass fraction, the lower the ceramic slurry viscosity and the better the fluidity. When the mass fraction is too low, the porosity of the prepared brushite matrix is ​​higher, but its mechanical properties are lower, which is not conducive to subsequent material preparation. In addition, the purpose of polyvinyl alcohol and sodium polyacrylate in the ceramic slurry is mainly to enhance the structural stability and mechanical properties of the brushite matrix.

[0035] In some embodiments, in step (2), the bi-directional freezing is carried out in a mold with the assistance of a wedge-shaped polydimethylsiloxane (PDMS) block; preferably, the angle of the wedge-shaped polydimethylsiloxane used for the bi-directional freezing can be 10-20°, more preferably 15°; the temperature of the bi-directional freezing can be -100 to -180°C, and the time of the bi-directional freezing can be 0.5-2h.

[0036] Double-directional freezing means that the water in a liquid under two temperature gradient conditions will preferentially freeze along the direction of the temperature gradient. Therefore, under two temperature gradient conditions (such as temperature gradients in the X and Z directions), water will preferentially freeze in the plane constructed by XZ, thereby achieving the orientation of ice crystals within one plane. When there is only one temperature gradient, ice crystals will only have directionality in one direction, and the other two directions are chaotic. However, when there are two temperature gradients, directional ice crystals will be formed in the plane constructed by the two temperature gradients, so this method is also called double-directional freezing. The angle is the key to achieving double-directional freezing. Only when there is an angle will two temperature gradients be formed, and the size of the angle controls the size of the temperature gradient. The larger the angle, the larger the temperature gradient, and the easier it is to form a directional structure. The smaller the angle, the smaller the temperature gradient, and the more difficult it is to obtain a directional structure.

[0037] In some embodiments, in step (2), the freeze-drying pressure may be 10-100 Pa, the temperature may be -30 to -50°C, and the time may be 24-72 hours; preferably, the freeze-drying is performed at 10 Pa and -30°C for 48 hours. Freeze-drying can remove ice crystals in the green body obtained after bi-directional freezing.

[0038] In some embodiments, in step (3), in the methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution, based on the total mass of methyl methacrylate and acrylic acid as 100%, the mass fraction of methyl methacrylate can be 90-95%, preferably 95%, and the mass fraction of acrylic acid can be 5-10%, preferably 5%; the mass fraction of the initiator can be 2-4%, preferably 2%, of the total mass of methyl methacrylate and acrylic acid. Within the specified range, the methyl methacrylate monomer can be well polymerized to obtain polymethyl methacrylate.

[0039] The mechanical properties of the shell-like bioceramic composite material can be further enhanced by adding acrylic acid to the prepared MMAA polymer mixture. Acrylic acid is a polymer monomer containing carboxyl groups, which can not only be miscible and copolymerized with methyl methacrylate monomers, but also with the Ca2+ of the brushite microsheets in the brushite matrix material. 2+ Combined with each other, a strong bonding force is formed, thereby further enhancing the mechanical properties of the composite material.

[0040] In some embodiments, in step (3), the vacuum infiltration process can be: placing the ordered layered porous structure brushite matrix template in a centrifuge tube and adding a methyl methacrylate (MMA)-acrylic acid (AA)-benzoyl peroxide (BPO) polymer mixed solution, and then placing them together in a vacuum drying oven, and evacuating them at 25-30°C and 80-100Pa vacuum for 7-9 hours.

[0041] Wherein, in the vacuum infiltration process, the usage ratio of the ordered layered porous structure brushite matrix template to the methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution can be 4-16mL:5-30mL.

[0042] In some embodiments, in step (3), the pre-curing is carried out under normal atmospheric pressure, at a temperature of 40-50° C., for 6-8 days, preferably 7 days. Methyl methacrylate is pre-cured into polymethyl methacrylate (PMMAA) by immersing the ordered layered porous structure brushite matrix template in a MMAA polymer mixture.

[0043] In some embodiments, in step (3), the pressing process can be: taking out the pre-cured block template material and pressing the block template material along a direction perpendicular to the layered structure using a powder tablet press; wherein the pressing pressure can be 125-305MPa, preferably 301MPa, and the pressing time can be 10-30min.

[0044] Fill the inside of the brushite matrix with a certain porosity with MMAA polymer mixed liquid, and press the block material after pre-curing. The internal MMAA polymer mixed liquid will be squeezed out. Therefore, different pressing pressures will be adopted to obtain bioceramic-based composite materials with different PMMAA contents. The greater the pressure used, the less PMMAA is retained, and the higher the mass fraction of brushite in the composite material; conversely, the smaller the pressure used, the more PMMAA is retained, and the lower the mass fraction of brushite in the composite material. In summary, the ratio of brushite and PMMAA in the shell-like structure bioceramic-based composite material can be regulated by adjusting the pressing pressure, thereby regulating the comprehensive mechanical properties of the composite material.

[0045] In some embodiments, in step (3), the secondary curing process may include: placing the pressed ordered layered porous structure brushite matrix template in a methyl methacrylate (MMA)-acrylic acid (AA)-benzoyl peroxide (BPO) polymer mixed solution, and then placing them in a vacuum drying oven, and evacuating them at 25-30°C and 80-100Pa vacuum for 3-5 hours to allow the MMAA polymer mixed solution to further penetrate into the block template material, and then continuing to cure at 40-50°C and normal atmospheric pressure for 6-8 days until the MMAA polymer mixed solution is cured into a solid state.

[0046] In some embodiments, in step (3), the drying temperature may be 60-80° C., preferably 70° C., and the drying time may be 3-5 hours, preferably 4 hours. Drying can ensure that the MMAA in the bulk material is completely solidified.

[0047] The present invention uses a double-directional freezing-freeze drying method to construct a brushite matrix with an ordered layered porous structure, then fills PMMAA inside it by vacuum infusion to make it dense, then uses a tablet press to compact it, and performs secondary curing of PMMAA. After thorough curing and drying, it is polished to prepare a shell-like structure bioceramic-based composite material. By imitating the "brick-mud" structure of shells, a high-strength and high-toughness natural material, using bioactive ceramic brushite as "bricks" and PMMAA as "mud", a shell-like structure bioceramic-based composite material is prepared, which is expected to obtain mechanical properties matching those of natural bone tissue.

[0048] Compared with the traditional bioceramics prepared by high-temperature sintering, the bioceramics prepared by the present invention have higher bending strength and lower bending modulus, which are close to the mechanical properties of human bone tissue and can better match bone tissue, thus overcoming the problem that traditional bioceramics are difficult to match bone tissue due to their high brittleness and high modulus. The acquisition of this excellent mechanical property is due to the shell-like structure design on the one hand, and the reinforcing effect of the filled polymethyl methacrylate on the other hand. During the fracture process, the material does not fracture instantaneously, but fractures layer by layer. This fracture mode can effectively increase energy dissipation and improve the toughness of the material. The bone mechanics matching shell-like structure bioceramic-based composite material obtained by the preparation method provided by the present invention not only has comprehensive mechanical properties that are relatively close to natural cortical bone, but can be better matched with bone tissue after being implanted in the body. At the same time, since the bioactive ceramic brushite can continuously release Ca and P bioactive ions, the bioceramic-based composite material also has good biological activity, which is beneficial to the repair and regeneration of bone tissue.

[0049] The bone mechanics matching shell-like structure bioactive ceramic-based composite material obtained by the preparation method provided by the present invention can be used in the preparation of bone repair materials.

[0050] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0051] Example 1

[0052] The preparation method of the bone mechanics matching shell-like structure bioactive ceramic matrix composite material provided in this embodiment comprises the following steps: (1) 1.650 g of potassium dihydrogen phosphate (KH2PO4) and 6.019 g of sodium dihydrogen phosphate (Na2HPO4) were successively added to a beaker containing 1.4 L of ultrapure water, and the mixture was placed in a constant temperature magnetic stirring water bath in an ice water bath (0°C) and magnetically stirred for 0.5 h; 6.062 g of anhydrous calcium chloride (CaCl2) was added to 0.4 L of ultrapure water, stirred to dissolve, and placed in ice water for later use; then, the prepared calcium chloride solution was slowly added to the mixed solution of potassium dihydrogen phosphate and sodium dihydrogen phosphate, and magnetically stirred in an ice water bath for 1 h. Stir for 1.5 hours; finally, filter with a vacuum pump, and place the resulting precipitate in a fume hood to dry naturally for more than 72 hours to remove excess moisture; grind and disperse the dried blocks in a mortar to obtain flaky brushite ceramic powder; further, ultrapure water, 10% flaky brushite powder, 2% polyvinyl alcohol (PVA) and 1% sodium polyacrylate (PAAS) are mixed together and magnetically stirred for 12 hours; the stirred ceramic slurry is placed in a freeze drying oven, and vacuumized for 5 minutes at room temperature to remove bubbles in the slurry to obtain brushite ceramic slurry. (2) The brushite ceramic slurry prepared in step (1) is poured into a mold, and a wedge-shaped (wedge angle of 15°) polydimethylsiloxane (PDMS) block is used as an auxiliary to prepare a frozen green body of a layered structure bioceramic block template material by double directional freezing; after the freezing is completed, the obtained frozen green body is quickly demolded and placed in a freeze dryer (~10Pa, -30°C) for freeze drying for more than 48 hours to remove ice crystals in the green body, thereby obtaining an ordered layered porous structure brushite matrix template, which is recorded as 10-BDF. (3) The ordered layered porous structure brushite matrix template prepared in step (2) is placed in a 50 mL centrifuge tube, and 30 mL of a polymer mixture MMAA composed of 95% MMA and 5% AA is added, and 2% of an initiator BPO is added; then the tube is placed in a freeze drying oven, and vacuumed for 8 hours at room temperature and a vacuum degree of 100 Pa to allow the MMAA polymer mixture to fully penetrate into the block template material; then, the centrifuge tube is sealed, and the block template material is continued to be immersed in the MMAA polymer mixture at 45° C. and normal atmospheric pressure for pre-curing for 7 days; then, a tablet press is used to press the block at a pressure of 301 MPa in a direction perpendicular to the layered structure. The template material is compressed; the block obtained after compression is immersed in the previous MMAA polymer mixture again, and evacuated in a vacuum drying oven at room temperature and a vacuum degree of ~100Pa for 4 hours to allow the MMAA polymer mixture to further fully penetrate into the block template material; thereafter, the curing is continued at 45°C and normal atmospheric pressure for 7 days until the MMAA polymer mixture is cured into a solid state; then, the block is transferred to a drying oven and heated at 70°C for another 4 hours to ensure that the MMAA in the block material is completely cured; after grinding and polishing, the bone mechanics matching shell-like structure bioactive ceramic-based composite material is obtained, which is recorded as 10-BDF-PMMAA-P301.

[0053] Example 2

[0054] The preparation method of the bone mechanics matching shell-like structure bioactive ceramic matrix composite material provided in this embodiment refers to that in embodiment 1, the main difference is that: the mass fraction of brushite in the ceramic slurry is 20%; The prepared ordered layered porous structure of calcium phosphate matrix template is recorded as 20-BDF, and the prepared shell-like layered ordered structure bioactive ceramic composite material is recorded as 20-BDF-PMMAA-P301.

[0055] Example 3

[0056] The preparation method of the bone mechanics matching shell-like structure bioactive ceramic matrix composite material provided in this embodiment refers to that in embodiment 1, the main difference is that: the mass fraction of brushite in the ceramic slurry is 30%; The prepared ordered layered porous structure of calcium phosphate matrix template is recorded as 30-BDF, and the prepared shell-like layered ordered structure bioactive ceramic composite material is recorded as 30-BDF-PMMAA-P301.

[0057] Comparative Example 1

[0058] The preparation method of the bioactive ceramic-based composite material provided in this comparative example refers to Example 1, with the main difference being that: in step (2), the ceramic slurry with a brushite mass fraction of 10% prepared in step (1) is directly placed in a -80°C refrigerator to prepare a frozen green body, and the frozen green body is then freeze-dried; The prepared disordered brushite matrix template was marked as 10-NDF, and the prepared disordered bioactive ceramic-based composite material was marked as 10-NDF-PMMAA-P301.

[0059] Comparative Example 2

[0060] The preparation method of the bioactive ceramic-based composite material provided in this comparative example refers to Example 1, with the main differences being: In step (3), the polymer mixed solution contains only MMA, and no AA is added; The prepared bioactive ceramic-based composite material was named 10-BDF-PMMA-P301.

[0061] Table 1 below is a comparison of the mechanical properties of the shell-like structure bioceramic-based composite material prepared in Example 1 and natural materials:

[0062] Figure 1 The microscopic morphology of the brushite ceramic powder prepared in Example 1 is shown in Figure A. The inserted picture is an optical photograph of the brushite ceramic powder. It can be seen from the figure that the brushite ceramic powder is in the form of flakes, with a size of 5-10 μm, a thickness of 300-500 nm, and is relatively uniform overall.

[0063] Figure 2 The crystal phase analysis diagram and thermogravimetric analysis diagram of the brushite ceramic powder prepared in Example 1; wherein A is the XRD spectrum of brushite, and B is the thermogravimetric curve of brushite. The XRD spectrum shows that the phase composition of the flaky powder is brushite phase (CaHPO4·2H2O); the thermogravimetric analysis results of the powder show that the weight loss of the powder in the range of room temperature to 300°C is 19.65%, and the peak values ​​of the differential thermal curve are 75.4°C, 160.9°C and 198.4°C respectively, and the weight loss in the range of 300 to 600°C is 4.25%, and the peak value of the differential thermal curve is 426.9°C, which is consistent with the thermal decomposition process of standard brushite powder.

[0064] Figure 3Optical photographs and microscopic morphologies of the ordered layered porous structure brushite matrix with different brushite mass fractions obtained by bidirectional freezing-freeze drying in Examples 1-3 and the disordered structure brushite matrix obtained by -80°C freezing-freeze drying in Comparative Example 1; wherein A1-A4 are optical photographs and microscopic morphologies of the disordered structure brushite matrix, B1-B4 are optical photographs and microscopic morphologies of the ordered layered porous structure brushite matrix with a brushite mass fraction of 10%, C1-C4 are optical photographs and microscopic morphologies of an ordered layered porous structure brushite matrix with a brushite mass fraction of 20%, D1-D4 are optical photographs and microscopic morphologies of an ordered layered porous structure brushite matrix with a brushite mass fraction of 30%; E and F are optical photographs of a small-sized matrix obtained by cutting an ordered layered porous structure brushite matrix with a brushite mass fraction of 10% and an optical photograph of a letter-shaped brushite matrix cut by a custom mold, respectively. It can be seen from the figure that the brushite matrix prepared by combining the dual-directional freezing-freeze drying method has a relatively regular ordered layered porous structure, while the brushite matrix prepared by simply freezing-freeze drying at -80°C presents a disordered porous structure, which is very different from the ordered layered porous structure.

[0065] Figure 4 The interlayer distance (A) and porosity (B) of the ordered layered porous structure brushite matrix with different brushite (DCPD) mass fractions in Examples 1 to 3. As can be seen from the figure, as the brushite mass fraction in the ceramic slurry increases, the interlayer distance of the brushite matrix decreases and the porosity of the matrix material decreases.

[0066] Figure 5The optical photographs and microscopic morphologies of shell-like bioactive ceramic-based composite materials and disordered bioactive ceramic-based composite materials prepared under the same brushite mass fraction but different pressure conditions and under the same pressure but different brushite mass fraction conditions are shown in Figure 1; A1-A6 are optical photographs and microscopic morphologies of disordered bioactive ceramic-based composite materials, B1-B6 are optical photographs and microscopic morphologies of ordered layered porous brushite matrix with a brushite mass fraction of 10% and a pressure of 301 MPa, C1-C6 are optical photographs and microscopic morphologies of ordered layered porous brushite matrix with a brushite mass fraction of 10% and a pressure of 21 5MPa, D1-D6 are the optical photographs and micromorphology of the ordered layered porous structure brushite matrix with a brushite mass fraction of 10% and a pressure of 129MPa, E1-E6 are the optical photographs and micromorphology of the ordered layered porous structure brushite matrix with a brushite mass fraction of 20% and a pressure of 129MPa, F1-F6 are the optical photographs and micromorphology of the ordered layered porous structure brushite matrix with a brushite mass fraction of 30% and a pressure of 129MPa. The cross-sectional SEM images of the bioceramic-based composites show that the brushite microsheets in the shell-like structured bioceramic composites are highly ordered in the horizontal direction, while the organic components MMA and AA copolymer PMMAA and the polymers PVA and PAAS added in the preparation of the block template material are jointly filled on the surface of the brushite ceramic microsheets and in the gaps between the sheets, thus forming a relatively dense shell-like "brick-mud" layered structured bioceramic composite.

[0067] Figure 6 for Figure 5 Thermogravimetric analysis results of different bioceramic matrix composite materials; A is the thermogravimetric curve of different bioceramic matrix composite materials, and B is the actual brushite content-theoretical brushite content curve of bioceramic matrix composite materials. It can be seen from the figure that the brushite mass fraction of the shell-like structure bioceramic composite material is in the range of 52.83-90.60%; under the condition that other preparation conditions remain consistent, the actual inorganic content (i.e. the proportion of DCPD bioceramic powder) of the shell-like composite materials prepared under different compression pressure conditions gradually increases with the increase of compression pressure, while the content of infiltrated PMMAA gradually decreases; in addition, under the same compression pressure conditions, the actual inorganic content of the shell-like composite materials prepared with different layered structure bioceramic block template materials increases with the increase of ceramic powder content in the ceramic slurry, while the content of infiltrated PMMAA gradually decreases.

[0068] Figure 7is the bending properties of bioceramic matrix composites with different structures / compositions; where A is the bending strength of bioceramic matrix composites with different structures / compositions, B is the bending modulus of bioceramic matrix composites with different structures / compositions, C is the fracture work of bioceramic matrix composites with different structures / compositions, and D is the bending stress-strain curve of bioceramic matrix composites with different structures / compositions. It can be seen from the figure that the bending strength, bending modulus and fracture work of the bioceramic matrix composites with shell-like layered ordered structure are higher than those of the corresponding disordered structure bioceramic matrix composites; the bioceramic matrix composites prepared by infiltration of PMMAA have significantly improved bending strength, bending modulus and fracture work compared with the bioceramic matrix composites prepared by simple infiltration of PMMA. In summary, the ordered layered "brick-mud" structure can significantly improve the comprehensive performance of the material, showing that the shell-like structure bioceramic-based composite material prepared by the method of dual-directional freezing-MMAA infiltration and pre-curing-compression-MMAA re-infiltration-final curing has the best comprehensive mechanical properties; in addition, with the increase of ceramic powder content in the calcium phosphate matrix, the flexural strength and modulus of the shell-like bioceramic-based composite material both show a gradual downward trend, while the fracture work has no significant change, which may be related to the orderliness of the micro-layered structure of the shell-like bioceramic-based composite material.

[0069] Figure 8 is the bending properties of bioceramic matrix composites with different structures / pressing pressures; where A is the bending strength of bioceramic matrix composites with different structures / pressing pressures, B is the bending modulus of bioceramic matrix composites with different structures / pressing pressures, C is the fracture work of bioceramic matrix composites with different structures / pressing pressures, and D is the bending stress-strain curve of bioceramic matrix composites with different structures / pressing pressures. It can be seen from the figure that with the increase of compression pressure, the bending strength of bioceramic matrix composites with shell-like layered structure is about 120MPa, which is equivalent to the strength of natural shells (80-135MPa) and can meet the strength required for human cortical bone load-bearing (50-150MPa); the bending modulus shows a trend of decreasing and then increasing with the increase of compression pressure, and the fracture work shows a trend of increasing first and then decreasing with the increase of compression pressure; in addition, the bending strength, modulus and fracture work of bioceramic matrix composites with shell-like structure with good layered structure are higher than those of bioceramic matrix composites with disordered structure.

[0070] Fig. 9is the bending properties of bioceramic matrix composites with different structures / compositions under wet conditions; wherein, A is the bending strength of bioceramic matrix composites with different structures / compositions under wet conditions, B is the bending modulus of bioceramic matrix composites with different structures / compositions under wet conditions, C is the fracture work of bioceramic matrix composites with different structures / compositions under wet conditions, and D is the bending stress-strain curve of bioceramic matrix composites with different structures / compositions under wet conditions. As can be seen from the figure, the flexural strength of the shell-like bioceramic-based composite material 10-BDF-PMMAA-P301 with a layered ordered structure decreased from 119.3±5MPa in the dry state to 73.4±3.1MPa in the wet state, a decrease of 38.5%, but it can still meet the mechanical strength requirements (50-150MPa) for load-bearing bone defect repair; in contrast, the flexural strength of the disordered structure 10-NDF-PMMAA-P301 decreased from 75.8±2.2MPa in the dry state to 21.3±2.9MPa in the wet state, a decrease of 71.9%. This may be because the calcium phosphate microsheets in the 10-BDF-PMMAA-P301 shell-like composite material with a layered ordered structure are arranged in an oriented, ordered, layered, densely packed manner, and the hydrophobic PMMA can also more fully penetrate and fill the gaps in its layers, making its residual In contrast, the arrangement of the pentaerythrite microsheets in 10-NDF-PMMAA-P301 is relatively disordered, and the disordered stacking of the sheets will produce a large number of micropores, which makes its mechanical strength decrease more significantly after being soaked in SBF; for the flexural modulus, the 10-BDF-PMMAA-P301 shell-like composite material decreased from 6.8±0.4GPa in the dry state to 1.4±0.2GPa in the wet state; while 10-NDF-PMMAA-P301 decreased from 3.2±0.3GPa in the dry state to 0.7±0.1GPa in the wet state, indicating that although the layered bionic structure cannot avoid the significant decrease in the modulus of the composite material in the wet state, it is beneficial to the improvement of the mechanical properties of the material in the wet state; for the work of fracture, 10-NDF-PMMAA-P301 decreased from 0.91±0.07kJ / m 2 , reduced to 0.62±0.14kJ / m in wet state 2 ; while the 10-BDF-PMMAA-P301 shell-like composite material was 1.15±0.33 kJ / m 2 , significantly increased to 1.95±0.26kJ / m in wet state 2 , which is 3.1 times that of 10-NDF-PMMAA-P301 in wet state, and can meet the fracture toughness required for load-bearing bone defect repair (fracture work is 0.098-6kJ / m 2The above results show that the strength and fracture work of the 10-BDF-PMMAA-P301 shell-like bioceramic composite in the wet state can still match the mechanical properties of human cortical bone, and its comprehensive mechanical properties are still much better than those of the disordered 10-NDF-PMMAA-P301 composite prepared by a similar method.

[0071] Fig.10 The figure is a comprehensive mechanical properties analysis of bioceramic-based composite materials under different composition / pressing pressure conditions; A is the relationship between the mass fraction of brushite and the flexural strength in bioceramic-based composite materials under different composition / pressing pressure conditions, B is the relationship between the flexural strength and the flexural modulus of bioceramic-based composite materials under different composition / pressing pressure conditions, C is the relationship between the fracture work and the flexural strength of bioceramic-based composite materials under different composition / pressing pressure conditions, and D is a comparison of the mechanical properties of the prepared shell-like structure bioceramic-based composite materials and other bone repair materials. It can be seen from the figure that for shell-like structure bioceramic-based composite materials, its flexural strength is negatively correlated with the content of brushite powder, and its flexural modulus is positively correlated with the flexural strength; and its flexural strength and rupture work also show a positive correlation, that is, with the increase of the fracture work of the composite material, the flexural modulus of the shell-like structure bioceramic-based composite material also shows a gradual increase trend.

[0072] The adhesion of bone marrow mesenchymal stem cells on shell-like structure bioceramic-based composite materials and disordered structure bioceramic-based composite materials is explored below: Two experimental groups were set up, namely 10-NDF-PMMAA-P301 (10-NDF) and 10-BDF-PMMAA-P301 (10-BDF). The specific steps were as follows: a shell-like structure bioceramic-based composite material with a size of 10×10×1 mm was placed in a 24-well plate, and 1 mL of rabbit bone marrow mesenchymal stem cells (rBMSCs) suspension (1 mL, 1×10 4 cellsmL -1 , a total of 1×10 4 Cell wells -1) to completely immerse the composite material and evenly distribute it in the well plate; a 24-well plate well with the same number of cells but without any composite material blocks was used as a blank control (Blank); the well plate after inoculation of cells was then placed in a cell culture incubator containing 5% CO2 at 37°C for culture; 1 day later, the cells were fixed with 4% paraformaldehyde solution for 30 minutes and then washed three times with PBS; then, 0.1% Triton-X-100 was added to permeate the cells for 5 minutes and then washed three times with PBS; then, 1% BSA in PBS solution was added to block the composite material blocks, and the BSA was removed after incubation at room temperature for 30 minutes; then, FITC was added, incubated at room temperature in the dark for 40 minutes, and then washed three times with PBS; then, DAPI was added, incubated at room temperature in the dark for 7 minutes, and then washed three times with PBS; then, fluorescence imaging with 488nm (FITC channel, green) and 405nm (DAPI channel, blue) excitation wavelengths of CLSM was used to analyze the adhesion of rBMSCs on different composite materials and well plates.

[0073] Fig.11 The adhesion of bone marrow mesenchymal stem cells on shell-like structure bioceramic-based composite materials and disordered structure bioceramic-based composite materials; A is the immunofluorescence staining of cells adhered to the bottom of the well plate, B is the immunofluorescence staining of cells adhered to the disordered structure bioceramic-based composite material, and C is the immunofluorescence staining of cells adhered to the shell-like structure bioceramic-based composite material. It can be seen from the figure that cells can achieve good adhesion on both materials, indicating that the materials have good cell compatibility.

[0074] The following is an investigation of the proliferation of bone marrow mesenchymal stem cells co-cultured with shell-like structure bioceramic-based composite materials and disordered structure bioceramic-based composite materials: Two experimental groups were set up, namely 10-NDF-PMMAA-P301 (10-NDF) and 10-BDF-PMMAA-P301 (10-BDF). The specific steps were as follows: a composite material with a size of 10×10×1 mm was placed in a 24-well plate; then, 1 mL of rBMSCs suspension (1 mL, 2×10 4 cellsmL -1 , a total of 2×10 4 Cell wells -1) so that the cell suspension completely immerses the composite material and is evenly distributed in the well plate; a 24-well plate well with the same number of cells but without any composite material blocks is used as a control (Blank); the well plate after inoculation of cells is then placed in a cell culture incubator containing 5% CO2 at 37°C for culture, and the culture medium is replaced every 2 days; and at 1, 3, 5 and 7 days, after removing the previous α-MEM complete culture medium, 800 μL of α-MEM complete culture medium containing 10% CCK-8 is added to each well; then, it is placed in a cell culture incubator and incubated for 2.5 hours, and the OD value of each well at 450nm is measured with a multifunctional microplate reader (n=4) to determine the proliferation of rBMSCs on composite material blocks with different structures; the test results of all samples are expressed as the measured OD value minus the OD value of the blank well (the well plate well with only α-MEM complete culture medium containing 10% CCK-8 solution but without any composite material and / or cells).

[0075] Fig.12 Schematic diagram of the proliferation of bone marrow mesenchymal stem cells co-cultured with shell-like structure bioceramic-based composite materials and disordered structure bioceramic-based composite materials. It can be seen from the figure that the ordered structure bioceramic-based composite materials have better biological activity than the disordered structure bioceramic-based composite materials and can promote cell proliferation better.

[0076] The following is an investigation of the Ca and P ion release of shell-like structure bioceramic-based composite materials and disordered structure bioceramic-based composite materials: Two experimental groups were set up, namely 10-NDF-PMMAA-P301 (10-NDF) and 10-BDF-PMMAA-P301 (10-BDF); the specific steps were as follows: a composite material with a size of 10×10×1mm was placed in a 5mL centrifuge tube; then, 1mL of α-MEM complete culture medium was added to each centrifuge tube to completely immerse the composite material block; and a centrifuge tube sample with only 1mL of α-MEM complete culture medium without any composite material block was used as a negative control (Blank); then the above centrifuge tubes were sealed with a cap and placed in a constant temperature shaker at 37°C for incubation; then, the culture medium in the centrifuge tube was collected and filtered on the 1st, 3rd, 5th and 7th days, and 1mL of α-MEM complete culture medium was added to the centrifuge tube again at each time point; the calcium ion and phosphate ion concentrations in the collected culture medium were tested by inductively coupled plasma atomic emission spectrometry (ICP-AES) (n=3) to evaluate the ion release of composite material blocks with different structures in the culture medium during cell culture.

[0077] Fig.13The figure shows the release of Ca and P ions from the shell-like structure bioceramic-based composite material and the disordered structure bioceramic-based composite material; A is the release of Ca ions from the two materials, and B is the release of P ions from the two materials. As can be seen from the figure, compared with the Blank group, the shell-like structure bioceramic-based composite material and the disordered structure bioceramic-based composite material can continuously release Ca and P, two bioactive ions, at a higher ion concentration level within 7 days, and compared with the disordered structure bioceramic-based composite material group, the shell-like structure bioceramic-based composite material has a significantly lower release rate of Ca and P ion concentration, which weakens the sudden release of high-concentration ions, thereby facilitating the proliferation of rBMSCs on the material and having good proliferation activity.

[0078] The following is an investigation of the integration of shell-like structure bioceramic-based composite materials and disordered structure bioceramic-based composite materials with native bone after implantation into rabbit skull defects: Two experimental groups were set up, namely 10-NDF-PMMAA-P301 (10-NDF) and 10-BDF-PMMAA-P301 (10-BDF). The specific steps were as follows: establish a skull defect model in New Zealand rabbits, first inject an appropriate dose of chloral hydrate solution into the ear vein to anesthetize the New Zealand rabbits, then use a shaver to remove the hair on the rabbit's head and disinfect it with iodine; use a scalpel to gently cut the skin on the head to expose the skull, cut the periosteum along the sagittal suture of the skull and use forceps to separate the periosteum; then use a 9mm diameter drill to establish skull defects on both sides of the sagittal suture; then implant a composite material block with a diameter of 9mm and a thickness of 1.5mm, suture the skin, and complete the modeling. Among them, the group with only the defect established but no implanted material was the blank group (Blank); after 12 weeks of implantation, the rabbits were killed and the implanted materials and surrounding skull tissues were removed together, and immersed in 4% paraformaldehyde for tissue fixation for subsequent histological analysis. The steps are as follows: dehydrate the retrieved tissue and embed it into a block with polymethyl methacrylate material, use a hard tissue slicer to cut the embedded block into slices with a thickness of 600 μm along the direction perpendicular to the layered structure of the material, grind and polish the slices for subsequent histological staining, heat the methylene blue-potassium permanganate solution and deionized water washing bottle in a 60°C water bath in advance, put the processed slices in a clean beaker, add ultrapure water to ultrasonically wash the slices for 30 seconds, and rinse the slices with ultrapure water for 2 minutes; after drying, soak the slices in 0.1% formic acid solution for 3 minutes, rinse the slices with running water for 2 minutes; place the slices in 20% methanol solution for 2 hours, rinse the slices with running water for 2 minutes; put the slices in methylene blue-potassium permanganate solution for staining for 10-60 seconds, rinse the slices with 60°C deionized water and wipe dry; add fuchsin-picric acid solution to cover the tissue, stain for 12 minutes, rinse with anhydrous ethanol for 2 minutes, and the staining is completed, and then observe the staining with an optical microscope.

[0079] Fig.14 This is a schematic diagram of the integration of shell-like structure bioceramic-based composite materials and disordered structure bioceramic-based composite materials with native bone after implantation into rabbit skull defect. As can be seen from the figure, shell-like structure bioceramic-based composite materials have good bone integration ability, laying a good foundation for the repair and regeneration of bone tissue.

[0080] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A bone mechanics matching shell-like structure bioactive ceramic matrix composite material, characterized in that: The bone mechanics matching shell-like structure bioactive ceramic matrix composite material comprises: an ordered layered porous structure bioceramic matrix, and a biocompatible polymer material uniformly distributed on the surface and inside of the ordered layered porous structure bioceramic matrix; The bioceramic elements of the ordered layered porous structure bioceramic matrix include brushite powder, aluminum oxide nanosheets, hydroxyapatite microrods, calcium silicate nanowires or graphene oxide nanosheets, preferably brushite powder; The biocompatible polymer material includes at least one of polymethyl methacrylate, polyvinyl alcohol, sodium polyacrylate, polyacrylamide and sodium alginate.

2. The bone mechanics matching shell-like structure bioactive ceramic-based composite material according to claim 1, characterized in that: Taking the total mass of the bone mechanics matching shell-like structure bioactive ceramic-based composite material as 100%, the mass of the ordered layered porous structure bioceramic matrix accounts for 70-75%, and the mass of the biocompatible polymer material accounts for 25-30%; Preferably, the mass proportion of the brushite matrix of the ordered layered porous structure is 70-75%, the mass proportion of polymethyl methacrylate is 8-10%, and the mass proportion of polyvinyl alcohol and sodium polyacrylate is 17-20%.

3. The bone mechanics matching shell-like structure bioactive ceramic-based composite material according to claim 1 or 2, characterized in that: The bone mechanics matching shell-like structure bioactive ceramic-based composite material has a flexural strength of 60-140 MPa, preferably 119.3±5 MPa; an elastic modulus of 2-7.5 GPa, preferably 6.8±0.4 GPa; and a fracture work of 0.82-1.75 kJ / m 2 , preferably 1.15±0.33 kJ / m 2 .

4. A method for preparing a bone mechanics matching shell-like structure bioactive ceramic-based composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing brushite powder, polyvinyl alcohol solution and sodium polyacrylate solution to obtain brushite ceramic slurry; (2) subjecting the brushite ceramic slurry to bi-directional freezing and freeze drying to obtain a brushite matrix template with an ordered layered porous structure; (3) Filling the ordered layered porous structured brushite matrix template with a methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution through a vacuum infiltration process and pre-curing, and then pressing, secondary curing, and drying to obtain the bone mechanics matching shell-like structure bioactive ceramic-based composite material.

5. The preparation method according to claim 4, characterized in that: In step (1), the brushite powder is prepared by the following process: potassium dihydrogen phosphate, disodium hydrogen phosphate and anhydrous calcium chloride are added to ultrapure water in sequence, a precipitation reaction occurs in the solution to generate brushite micron flakes, and the brushite ceramic powder is obtained by suction filtration, drying, grinding and dispersion; wherein the mass ratio of the ultrapure water, potassium dihydrogen phosphate, disodium hydrogen phosphate and anhydrous calcium chloride is 0.9-3.6L:0.825-3.3g:3.0095-12.038g:3.031-12.124g, preferably 1.8L:1.650g:6.019g:6.062g; In the brushite ceramic slurry, the mass fraction of brushite is 10-30%, preferably 10%; the mass fraction of polyvinyl alcohol is 1-5%, preferably 2%; and the mass fraction of sodium polyacrylate is 0.5-1%, preferably 1%.

6. The preparation method according to claim 4 or 5, characterized in that: In step (2), the bi-directional freezing is carried out in a mold with the aid of a wedge-shaped polydimethylsiloxane block; preferably, the angle of the wedge-shaped polydimethylsiloxane used for the bi-directional freezing can be 10-20°, more preferably 15°; the temperature of the bi-directional freezing is -100 to -180°C, and the time of the bi-directional freezing is 0.5-2h.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (3), in the methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution, based on the total mass of methyl methacrylate and acrylic acid as 100%, the mass fraction of methyl methacrylate can be 90-95%, preferably 95%, and the mass fraction of acrylic acid is 5-10%, preferably 5%; the mass fraction of the initiator benzoyl peroxide can be 2-4% of the total mass of methyl methacrylate and acrylic acid, preferably 2%.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (3), the vacuum infiltration process is as follows: placing the ordered layered porous structure brushite matrix template in a centrifuge tube and adding a methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution, and then placing the mixture in a vacuum drying oven, and evacuating the mixture at 25-30° C. and 80-100 Pa for 7-9 hours; The pre-curing is carried out under normal atmospheric pressure, at a temperature of 40-50°C, for 6-8 days, preferably 7 days; The pressing process is: taking out the pre-cured block template material and pressing the block template material along a direction perpendicular to the layered structure using a powder tablet press; wherein the pressing pressure is 125-305MPa, preferably 301MPa, and the pressing time is 10-30min.

9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (3), the secondary curing process comprises: placing the pressed ordered layered porous structure brushite matrix template in a methyl methacrylate-acrylic acid-benzoyl peroxide polymer mixed solution, and then placing them in a vacuum drying oven, evacuating for 3-5 hours at 25-30° C. and 80-100 Pa vacuum degree to allow the MMAA polymer mixed solution to further penetrate into the block template material, and then continuing to cure at 40-50° C. and normal atmospheric pressure for 6-8 days until the MMAA polymer mixed solution is cured into a solid state.

10. Use of the bone mechanics matching shell-like structure bioactive ceramic-based composite material according to any one of claims 1 to 3 in the preparation of bone repair materials.